General Direct Anticancer Effects of Deer Growing Antler Extract in Several Tumour Cell Lines, and Immune System-Mediated Effects in Xenograft Glioblastoma - Alessandra Rossetti; Louis Chonco; Nicolas Alegría; Veronica Zelli; Andrés J. García; Carmen Ramírez-Castillejo; Alessandra Tessitore; Carlos de Cabo; Tomás Landete-Castillejos; Claudio Festuccia (MDPI AG, 2024)
Deer antlers are the fastest growing tissue. Because they are based on proto-oncogenes, to avoid the risk of cancer, antlers evolved strong anticancer mechanisms, and thus their extract (DVA) is effective also against the few human tumours studied so far. We assessed whether DVA is a general anticancer compound by testing the direct effects in cells of different tumours: glioblastoma (GBM; lines U87MG and U251), colorectal (CRC; lines DLD-1, HT-29, SW480, and SW620), breast cancer (BRCA; lines MCF7, SKBR3, and PA00), and leukaemia (THP-1). DVA reduced the viability of tumours but not healthy cells (NHC; lines 293T and HaCaT). Mobility decreased at least for the longest test (72 h). Intraperitoneal/oral 200 mg DVA/kg administration in GBM xenograft mice for 28 d reduced tumour weight by 66.3% and 61.4% respectively, and it also reduced spleen weight (43.8%). In addition, tumours treated with DVA showed symptoms of liquefactive necrosis. Serum cytokines showed DVA up-regulated factors related to tumour fighting and down-regulated those related to inducing immune tolerance to the tumour. DVA shows general anticancer effects in the lines tested and, in GBM mice, also strong indirect effects apparently mediated by the immune system. DVA may contain a future anticancer medicine without secondary effects.